Preparação de substratos de carbeto de silício para fins aeroespaciais - Dini, George Henrique [UNESP] (2013)
This conclusion thesis has the objective of produce substrates of Silicon Carbide from the powder of SiC for aerospace use. The powder of SiC was pressed in cylindrical form by the process called “wet way”. For the inicial pressing process was used a uniaxial squeezer and after that was used a isostatic squeezer, after that the samples were synthesized. The next step was the machining and polishing to improve the features of the surface of the sample. Then the roughness was measured, as also the Arquimedes method and optical microscopy and scanning eletron microscopy. Some innovations were done, in one of the lots little vacancys were done with organic material or silicon to reduce the weight of the sample; and the other innovation were the use of a slip film of SiC on the surface of the sample, that were after synthesized with LASER to reduce the roughness, in this samples the roughness were reduce in 50 % if compared with the other samples